Convenient and sensitive colorimetric detection of melamine in dairy products based on Cu(ii)-H2O2-3, 3′, 5, 5′-tetramethylbenzidine system. Issue 61 (11th October 2018) - Han, Xue; Qin, Zhixin; Zhao, Mengyao; Song, Jiajia; Qu, Fei; Qu, Fengli; Kong, Rong-Mei
Abstract : Convenient and sensitive colorimetric detection of melamine in dairy products based on a Cu(ii )-H2 O2 -3, 3′, 5, 5′-tetramethylbenzidine system was reported. Abstract : The illegal adulteration of melamine in dairy products for false protein content increase is a strong hazard to human health. Herein, a simple and sensitive colorimetric method was developed for the quantification of melamine in dairy products based on a Cu 2+ -hydrogen peroxide (H2 O2 )-3, 3′, 5, 5′-tetramethylbenzidine (TMB) system. In this strategy, Cu 2+ exhibits peroxidase-like activity and can catalyze the oxidation of TMB to oxidized TMB (oxTMB) in the presence of H2 O2 with a blue colour change of the solution. However, the presence of melamine quickly interacts with H2 O2 leading to the consumption of H2 O2 and thus strongly hinders the oxidation of TMB. Under the optimal conditions, the absorbance change of oxTMB has a linear response to the concentration of melamine from 1 to 100 μM with a detection limit of 0.5 μM for melamine. The proposed method has many merits including more simplicity, good selectivity, and more cost-effectiveness without using any nanomaterials. The method was further successfully applied to detect melamine in dairy products including milk and infant formula powder.